Experience of Reality a Conceptual Framework and its Implications (London Journal of Research In Humanities and Social Sciences, 2025)
The experience of reality (EoR) is a relevant part of our everyday conscious experience. It holds the potential to shape reasoning, reporting, and acting. On the one hand, EoR helps us to navigate towards our goals. On the other hand, it can be used as a tool for social control and manipulation. Here, I propose a distinction between three types of EoR: EoR out there, EoR of the experience itself and EoR somehow, and I put forward two key ideas concerning EoR. First, I argue for the idea that EoR is not always aligned with reality. In other words, what we experience as real does not always correspond to what is really the case. Luckily, this misalignment can be reduced throughout both non-interactive and interactive dynamics. Second, I identify one exception to this rule: EoR somehow lacks content and is entirely undetermined and non-conceptualized. Hence, it always aligns with the reality it is an experience of.
Keywords: Reality.; perceptual presence; experience of reality; subjective veridicality; process; pure consciousness states